Influence of Kakwa Culture on Child Abuse in Kululu Sub-county Yumbe District Northern Uganda - Stephen Bidali (Uganda Christian University, 2024)
The study examined the influence of Kakwa culture on child abuse in Kululu sub-county Yumbe district northern Uganda. Specifically, the study identified specific cultural practices that may be harmful to children, explored the influence of indigenous language on prevention of child abuse and examined the cultural norms, values that prevent abuse of children. The target population was 50, Out of the target population, a sample size of 44 subjects were drawn. The study utilized a descriptive survey research design since a sample out of a target population was used. Questionnaires were employed to draw information from teachers and pupils while, an interview schedule was employed to gather data from the school head teachers. The data collected was analyzed using descriptive statistics such as frequencies, means and standard deviations. The qualitative data was summarized and analyzed using themes and categories derived from the responses. The analysis of the results indicated that the key harmful cultural practices in kakwa culture were extraction of milk teeth, Uvula cutting of the throat with a sharp object and forced marriages of young girls. The study found that the aspects of indigenous language that can contribute to prevention of child abuse included: Communication with children in indigenous language, builds trust, and provides support, Indigenous Language improves the positive perceptions of child protection, and indigenous language helped children learn how to take care of themselves and learning indigenous Language safely guided children in communities. It was concluded that Overall, the most frequently reported harmful cultural practices in Kakwa culture were extraction of milk teeth, Uvula cutting of the throat with a sharp object and forced marriages of young girls. However, not all cultural norms or values contribute to child abuse in Kakwa cultural. Basing on the findings the study recommended that; there is need to create awareness of the values and norms among parents and the entire Community. Ample training, therefore, should be provided for community cultural leaders through adult literacy clubs, and community learning centers to improve their literacy on children rights. Social workers should endeavor to foster collaboration among house hold heads and cultural heads in Sub County so as to promote the sharing of best cultural practices.